Student's Emotional Experience and Social Interaction Using Zoom Platform for Online Learning During COVID-19 Pandemic/ Pengalaman Emosional dan Interaksi Sosial Mahasiswa Dalam Menggunakan Sarana Zoom untuk Pembelajaran Online selama Pandemi COVID-19 - Nurwijayanti, Nurwijayanti; Lessy, Zulkipli; Sari, Onica; Erdiani, Nila; Khaja, Khadija (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2022)
The Covid-19 pandemic has affected the learning and teaching process at universities around the world. To address this crisis, many universities are switching from face-to-face learning to distance learning. They replaced face-to-face (FTF) instruction with classes taught by means of online platforms, so that teachers and students could remain academically productive even when not meeting in person. The sudden and rapid adaptation during the Covid-19 pandemic has created very significant transformations and challenges for the world of higher education globally. This study analyzes self-reported experiences of students using the Zoom platform for online learning in English as a Foreign Language (EFL) classrooms during the pandemic, and it assesses the extent to which the Zoom platform satisfied students’ expectations. Data was collected from seventeen students majoring in English Education at a higher education institution during the fourth semester of the 2019/2020 academic year. The instrument is questionnaires. Qualitative data were obtained by means of a questionnaire and an essay of students’ reflections. Data analysis was conducted by examining five aspects of responses based on indicators from the appraisal: intrinsic pleasure, novelty, the significance of goals/needs, coping potential, and norms/self-conformance. The study revealed that students found many benefits but encountered difficulties or barriers in using the Zoom platform for online learning during Covid-19. Abstrak Pandemi Covid-19 telah mempengaruhi proses belajar dan mengajar di berbagai universitas di seluruh dunia. Untuk mengatasi krisis ini, banyak universitas beralih dari pembelajaran tatap muka ke pembelajaran jarak jauh. Mereka mengganti pembelajaran tatap muka dengan kelas yang diajarkan melalui sarana online sehingga dosen dan mahasiswa tetap produktif secara akademis bahkan ketika tidak bertemu langsung. Proses adaptasi yang cepat di masa pandemi Covid-19 ini telah menciptakan baik perubahan maupun tantangan yang sangat signifikan bagi dunia perguruan tinggi secara global. Studi ini menganalisis pengalaman mahasiswa yang dilaporkan sendiri tentang penggunaan sarana Zoom untuk pembelajaran online di kelas Bahasa Inggris sebagai Bahasa Asing (EFL) selama pandemi, dan menilai sejauh mana sarana Zoom memenuhi harapan mahasiswa. Data dikumpulkan dari tujuh belas mahasiswa jurusan Pendidikan Bahasa Inggris di perguruan tinggi pada semester keempat tahun ajaran 2019/2020. Instrumennya adalah kuesioner. Data kualitatif diperoleh melalui angket dan essai refleksi mahasiswa. Analisis data dilakukan dengan menguji lima aspek tanggapan berdasarkan indikator penilaian: kesenangan intrinsik, kebaruan, signifikansi tujuan/kebutuhan, mengatasi potensi, dan norma/kesesuaian diri. Studi ini mengungkapkan bahwa mahasiswa menemukan banyak manfaat tetapi juga mengalami kesulitan atau hambatan dalam menggunakan sarana Zoom untuk pembelajaran online selama Covid-19.